(untitled) (Research, Society and Development, 2020)
Pilocytic astrocytoma (PA) is a typically circumscribed, slow-growing tumor, being the most common glioma in children, usually originating in the cerebellum; there are few reports of this tumor in adults, but it has a good prognosis. Here, we report an PA diagnosis in an adolescent patient whose only complaint was progressive headache and presyncope. Given that it is essential to recognize the image pattern of a little aggressive pilocytic astrocytoma (grade 1), as it can be similar to high-grade gliomas, leading to more aggressive treatments mistakenly, we review the role of imaging methods in the diagnosis of PA.